Backreacted Coulomb energy in the Skyrme model - Sven Bjarke Gudnason; James Martin Speight (Journal of High Energy Physics)
Abstract The Skyrme model is extended with the Maxwell action and a source term for the gauge field. We consider the specialized case of vanishing isospin states, such that only an electric potential is turned on and study the backreaction onto the Skyrme fields. In particular, we study Skyrmions with baryon numbers B = 4, 8, 12, 16 and 40. We find, in agreement with physical expectations, that the Coulomb backreaction is most pronounced for large Skyrmions and find furthermore that the dynamics of the theory is more sensitive to the backreaction than the ground states (global minimizers of the energy). Calibrating the model to Carbon-12, we find excellent agreement of the masses of the studied Skyrmions — within 1.86% of experimental data. The Coulomb energies are slightly larger than phenomenological fits suggest, but only by about 3 – 22%, whereas the radii are within 15% errors, with the largest errors on the smallest baryon number (B = 4) and the smallest errors on the large baryon numbers.